2017
DOI: 10.5751/es-09054-220121
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of biophysical conditions on wildland–urban interface homeowners’ wildfire risk mitigation activities in fire-prone landscapes

Abstract: ABSTRACT. Expansion of the wildland-urban interface (WUI) and the increasing size and number of wildfires has policy-makers and wildfire managers seeking ways to reduce wildfire risk in communities located near fire-prone forests. It is widely acknowledged that homeowners can reduce their exposure to wildfire risk by using nonflammable building materials and reducing tree density near the home, among other actions. Although these actions can reduce the vulnerability of homes to wildfire, many homeowners do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…(1) Shared understanding: Risk perception is one important influence on wildfire risk reduction behavior among landowners and homeowners (McCaffrey 2008, Fischer and Charnley 2012, Olsen et al 2017. Family forest owners who participated in our cases perceived a high level of concern about wildfire occurring on their property and spreading to their property from adjacent ownerships (unpublished survey data), as did public landowners interviewed.…”
Section: Discussionmentioning
confidence: 96%
“…(1) Shared understanding: Risk perception is one important influence on wildfire risk reduction behavior among landowners and homeowners (McCaffrey 2008, Fischer and Charnley 2012, Olsen et al 2017. Family forest owners who participated in our cases perceived a high level of concern about wildfire occurring on their property and spreading to their property from adjacent ownerships (unpublished survey data), as did public landowners interviewed.…”
Section: Discussionmentioning
confidence: 96%
“…We did not report the results of actions by homeowners to adopt defensible space behaviors that reduce risk at the homesite scale. Olsen et al (2017) found that almost 80% of the homes in the study area adopted some component of defensible space practices, and that these actions were more likely in locations characterized by heighted fire hazard, suggesting that a high level of risk mitigation occurs across the population of homes. Our results suggest that land management actions in this area can reduce the potential for losses.…”
Section: Discussionmentioning
confidence: 99%
“…In hindsight, we may have been overly ambitious in this Ecology and Society 22(3): 25 https://www.ecologyandsociety.org/vol22/iss3/art25/ goal at the outset given the relative lack of available research on key network components, structure, and function. Although we did find statistically significant social network effects in our actor behavior models for family forest owners and homeowners (e.g., Olsen et al 2017), we were unable to fully represent these in the ABM because of limitations in our ability to model changes in social networks themselves. Difficulties arose mostly because we did not collect empirical information that described interactions among social network dynamics, actor behavior, and landscape change.…”
Section: What We Learned About Actor Behavior and How To Represent Itmentioning
confidence: 97%
“…For each actor group, substudies sought to (1) examine the landscape management activities that actors undertake; (2) explain actors' decision-making processes, including their goals, decision frameworks (e.g., policy directives), and wildfire risk perceptions; (3) identify biophysical and social factors that influence actors' forest management and wildfire risk mitigation behaviors; and (4) use these data to develop decision rules to be programmed into the ABM to represent actors' behaviors. Additional details about some of these individual substudies can be found in , Olsen et al (2017), and Steen-Adams et al (2017). The result was the application of a mix of methodological approaches to examine the forest management and wildfire risk mitigation behaviors of the different actor groups.…”
Section: How We Conducted Our Social Science Workmentioning
confidence: 99%
See 1 more Smart Citation